The Ability of a Child's Self-rating Scale in Estimating Intellectual Ability - Mohd Isa, Abd Majid (Universiti Putra Malaysia Press, 1996)
There is substantial evidence for non-intellectual factors to be considered as an additional criterion in the appraisal of intellectual ability. Therefore, the development of a child's self-rating scale has been intensive in the last decades. One of the most widely used self-rating scales is the School Feeling and Thought (SFT) scale. Bearing in mind that the SFT was developed in America, it is essential to undertake a study to ascertain whether the Malay versions of these instruments have the ability to assess intellectual ability of Malay children. The Malay version of SFT was administered to 100 Primary Six pupils (53 boys and 47 girls) from a single school in Tampin. The intellectual ability (IQ) was measured using the revised version of Wechsler Intelligence Scale for Children (WISC-R). The correlations between the SFT scores and the WISC-R full-scale IQ are modest. Two subtests of SFT, namely 'Action' and 'Affect', are found to be significant predictors of IQ The equation derived from multiple regression analysis to estimate IQ using SFT subtest scores is found to be able to predict intellectual ability (IQ). The only limitation is that the IQ predicted by this equation has an II-point error. Therefore, SFT can be used to estimate IQ and thus can be used as a screening test for intellectual ability of Malay children